2009
DOI: 10.1007/s11033-009-9804-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ADAR1’s regulation on lymphocyte cell function during rejection

Abstract: The RNA editing adenosine deaminase gene (ADAR1) expression is wide-spread in lymphocytes. We explore the mechanism of ADAR1 regulation on the function of T primary lymphocytes when rejection occurs by knock-down the expression of ADAR1 in mouse T primary lymphocytes in mixed lymphocyte cultures. The changes of cell proliferation, the expression of ADAR1 and the cell cycle related genes cyclin D1 and A1, cell cycle and apoptosis analysis and mouse gene expression profiles was evaluated. We found that treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, because editing levels were not assessed in these animals, it remains unknown what distinct function, if any, p150 serves in the editing of specific RNA targets. As p150 has been implicated in numerous cellular activities which are either editing-independent or involve unknown substrates (Cai et al, 2010; Herbert et al, 2002; Nie et al, 2005; Wang et al, 2006; Wang and Samuel, 2009; Zhang and Rabinovici, 2007), the precise functional role(s) for this ADAR1 isoform remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…However, because editing levels were not assessed in these animals, it remains unknown what distinct function, if any, p150 serves in the editing of specific RNA targets. As p150 has been implicated in numerous cellular activities which are either editing-independent or involve unknown substrates (Cai et al, 2010; Herbert et al, 2002; Nie et al, 2005; Wang et al, 2006; Wang and Samuel, 2009; Zhang and Rabinovici, 2007), the precise functional role(s) for this ADAR1 isoform remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the role of RNA editing and ADARs in immune function. Recent studies have identified ADAR1 as an essential regulator of hematopoietic stem cell maintenance and suppressor of interferon signaling [ 22 ] and as a dominant player in the regulation of primary T lymphocytes function during acute transplant rejection [ 23 ].…”
Section: Introductionmentioning
confidence: 99%